Pedagogy transdisciplinary a necessity in times of uncertainty - Flórez Villamizar, Libardo (Universidad Francisco de Paula Santander, 2015)
Society in recent times is characterized by daily dealing with changes, transformations, advances, and innovations; that in one way or another impact on man and each of the sectors that make up the social network. From there, the interest to reflecting on a fundamental aspect from which emerges a cluster of elements that could generate contributions for meaningful development in society; as it is the Trans-disciplinary Pedagogy with a broad, deep and epistemic look that is the basis of an education that understands and perceives the current dynamics that serve to prepare and train the men and women of the future that can be successfully developed in times where uncertainty takes over humanity and knowledge is confronted with new styles of thoughts and a rethinking adjusted to the demands of contemporary man. It is time, to go beyond every day to establish a dialogue between knowledge, about overcoming the barriers of wisdom; where pure knowledge loses its validity and absolute truth trembles before the changes, challenges, and transformations of humanity; This way, the pedagogical action can be resized through a Trans-disciplinary Pedagogy.